Appreciation in english tourism advertisements: an appraisal analysis - Phùng Thị Thúy Như (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to examine ―appreciation‖ in tourism advertisements in terms of its syntactic and semantic features. Furthermore, it also expects to provide a deeper understanding of the language use in tourism advertisements on the mass media, which aims to help non-native English speakers use this type of texts and language teachers effectively teach tourism English